Galois conections, chu mappings and bonds (2014)
In this paper we characterize bonds, as defined by Wille, by employing a less rigid set of axioms thus enabling the definition of the category BOND. Since bonds generalize Chu mappings we present a faithful functor between CHU and BOND. Moreover, we propose the Galois morphisms generalizing bonds; this allows us to define the category MGI. Lastly, we suggest a general method to construct categories of adjunctions from any given category. The category of adjunctions generated from the category of order-preserving Galois connections, namedMGP, turns out to be equivalent to the category MGI.